2016
DOI: 10.1016/j.juro.2015.10.181
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Prostate Convective Water Vapor Energy Ablation: A Multicenter, Randomized, Controlled Study for the Treatment of Lower Urinary Tract Symptoms Secondary to Benign Prostatic Hyperplasia

Abstract: Convective water vapor thermal therapy provides rapid and durable improvements in benign prostatic hyperplasia symptoms and preserves erectile and ejaculatory function. Treatment can be delivered in an office or hospital setting using oral pain medication and is applicable to all prostate zones including the median lobe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
207
3
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(231 citation statements)
references
References 9 publications
14
207
3
7
Order By: Relevance
“…The results from this open-label study of convective RF water vapor thermal therapy are consistent with the recently published results from a randomized study with a similar reduction in IPSS at 1 year (−11.7 vs. −12.5 points observed in the present study) 13. This provides evidence of stability and durability for this minimally invasive thermal procedure with a continuing IPSS reduction of 12.1 points at 2 years.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results from this open-label study of convective RF water vapor thermal therapy are consistent with the recently published results from a randomized study with a similar reduction in IPSS at 1 year (−11.7 vs. −12.5 points observed in the present study) 13. This provides evidence of stability and durability for this minimally invasive thermal procedure with a continuing IPSS reduction of 12.1 points at 2 years.…”
Section: Discussionsupporting
confidence: 92%
“…Analyses of randomized, controlled clinical trials for LUTS/BPH with drugs, endoscopic procedures, and surgeries have shown that placebo effects are to be considered in evaluating the outcomes of active treatments 21,22. However, as the improvements in IPSS and Q max in this study are comparable to those observed in the prospective, controlled pivotal convective RF thermal therapy trial, and similarly durable,13 the validity of the therapeutic responses are substantiated.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…A registration-directed pivotal, randomized controlled trial (Rezūm II RCT) of the convective RF water vapor thermal therapy was conducted to evaluate the effectiveness and safety of the Rezūm System for the treatment of men with moderate-to-severe LUTS associated with BPH 19. The study compared thermal therapy with a control/sham procedure of rigid cystoscopy and simulated active treatment sounds.…”
Section: Clinical Evidence For Convective Rf Water Vapor Thermal Therapymentioning
confidence: 99%